Improving swallowing function in a child with cerebral palsy: A single case study on the efficacy of intervention strategies - Kapoor, Priya; Manchanapura Shivalingaiah, Shrunga (Indian Journal of Child Health, 2024)
The study explored the efficacy of Oromotor exercises and proprioceptive neuromuscular facilitation (PNF) to improve swallowing abilities pre- and post-behavioral intervention in a child with cerebral palsy (CP). A 4-year-old female child diagnosed with global developmental delay secondary to spastic quadriplegic CP and poor feeding skills was taken up for study. Oro-motor stimulation and PNF with taste, temperature, and texture were used. Therapy was given twice a week for 30 min. Pre- and post-intervention, a detailed Oro motor and feeding evaluation was performed. Post-therapy evaluation revealed significant increase in body weight, oromotor movements, International Dysphagia Diet Standardization Initiative, Eating Drinking Ability Classification System level, frequency of water, and meal intake. The intense application of oromotor and PNF stimulation seemed to have effected significant improvements in feeding and swallowing abilities which translated to increased weight and positive parental feedback. This might have been responsible for positive outcomes seen in the present study as well.